Pengaruh Academic Self-Efficacy dan Dukungan Sosial Terhadap Academic Burnout - Cantri Ari Cahyaningtias; Muhammad Arif Budiman Sucipto; Sri Adi Nurhayati (Jurnal Bimbingan dan Konseling Ar-Rahman, 2025)
Stress coping is an important mechanism in dealing with psychological pressure, especially for students from broken homes. Family disharmony can cause emotional stress that affects learning motivation. The method employed is a quantitative approach with an ex post facto research design and a comparative approach. The sample determination was carried out using a purposive sampling technique calculated using the Isaac Michael formula. The population size was 40, and the sample consisted of 36 students from broken homes, with 18 males and 18 females, respectively. Validity and reliability tests were carried out on different samples, with a Cronbach's Alpha value of 0.947, which indicates that the instrument is highly reliable. Data collection techniques used questionnaires, observation, and documentation. Data were analyzed using the T-test, namely the Independent Sample t-Test shows a significance value (Sig. 2-tailed) of 0.006, which is below the threshold of 0.05. Thus, it can be concluded that there is a statistically significant difference between male and female stress coping.. The prerequisite test used the normality test with the Shapiro-Wilk method and the homogeneity test with Levene's Test. The results of the study indicate that students' stress coping is in the moderate to high category, and there is a significant difference between the stress coping of male and female students from broken homes. The proposed service used is Group Guidance with a Group Discussion Method. ___________________________________________________________________Coping stres merupakan mekanisme penting dalam menghadapi tekanan psikologis, terutama bagi peserta didik dari keluarga broken home. Ketidakharmonisan dalam keluarga dapat menimbulkan tekanan emosional yang berpengaruh pada motivasi belajar. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis ex post facto dan desain komparatif. Sampel ditentukan dengan purposive sampling melalui rumus Isaac & Michael, dari populasi 40 peserta didik diperoleh 36 responden, terdiri atas 18 laki-laki dan 18 perempuan. Instrumen penelitian diuji validitas dan reliabilitasnya pada sampel berbeda, dengan nilai Cronbach’s Alpha 0,947 yang menunjukkan reliabilitas tinggi. Data dikumpulkan melalui angket, observasi, dan dokumentasi. Hasil analisis menggunakan Independent Sample T-Test memperoleh nilai signifikansi 0,006 < 0,05, sehingga terdapat perbedaan signifikan antara coping stres laki-laki dan perempuan. Uji prasyarat meliputi normalitas Shapiro-Wilk dan homogenitas Levene’s Test yang menunjukkan data memenuhi syarat. Hasil penelitian memperlihatkan coping stres berada pada kategori sedang hingga tinggi. Penelitian ini merekomendasikan bimbingan kelompok dengan metode diskusi sebagai strategi pendampingan sesuai kebutuhan gender untuk mendukung motivasi belajar peserta didik broken home.